TLR2 and TLR4 polymorphisms influence mRNA and protein expression in colorectal cancer - Proença, Marcela Alcântara [UNESP]; Oliveira, Juliana Garcia de; Cadamuro, Aline Cristina Targa [UNESP]; Succi, Maysa [UNESP]; Netinho, João Gomes; Goloni-Bertolo, Eny Maria; Pavarino, Érika Cristina; Silva, Ana Elizabete [UNESP] (Baishideng Publishing Group Inc, 2015)
AIM: To evaluate the effect of promoter region polymorphisms of toll-like receptor (TLR)2-196 to -174del and TLR4-1607T/C (rs10759932) on mRNA and protein expression in tumor tissue and of TLR4+896A/G (rs4986790) on colorectal cancer (CRC) risk.METHODS: The TLR2-196 to -174del polymorphism was investigated using allele-specific polymerase chain reaction (PCR) and the TLR4-1607T/C and TLR4+896A/G by PCR-restriction fragment length polymorphism (RFLP). We genotyped 434 DNA samples from 194 CRC patients and 240 healthy individuals. The mRNA relative quantification (RQ) was performed in 40 tumor tissue samples by quantitative PCR TaqMan assay, using specific probes for TLR2 and TLR4 genes, and ACTB and GAPDH reference genes were used as endogenous controls. Protein expression was analyzed by immunohistochemistry with specific primary antibodies.RESULTS: No association was found for TLR4-1607T/C and TLR4+896A/G by three statistical models (log-additive, dominant and recessive). However, based on dominant and log-additive models, the polymorphic variant TLR2-196 to -174del was associated with increased CRC risk [dominant: odds ratio (OR) = 1.72, 95% CI: 1.03-2.89; P = 0.038 and log-additive: OR = 1.59, 95% CI: 1.02-2.48; P = 0.039]. TLR2 mRNA expression was increased in tumor tissue (RQ = 2.36) when compared to adjacent normal tissue (RQ = 1; P < 0.0001), whereas the TLR4 mRNA showed a basal expression (RQ = 0.74 vs RQ = 1, P = 0.452). Immunohistochemistry analysis of TLR2 and TLR4 protein expression was concordant with the findings of mRNA expression. In addition, the TLR2-196 to -174del variant carriers showed mRNA relative expression 2.19 times higher than wild-genotype carriers. The TLR2 protein expression was also higher for the TLR2-196 to -174del variant carriers [117 +/- 10 arbitrary unit (a.u.) vs 95 +/- 4 a.u., P = 0.03]. However, for the TLR4 -1607T/C polymorphism no significant difference was found for both mRNA (P = 0.56) and protein expression (P = 0.26).CONCLUSION: Our findings suggest that TLR2-196 to -174del polymorphism increases TLR2 mRNA expression and is associated with higher CRC risk, indicating an important role in CRC genetic susceptibility.
Keywords: Toll-like receptor 2; Toll-like receptor 4; Colorectal cancer; Protein expression; Gene expression; Genetic polymorphisms